2002
DOI: 10.1017/s0025315402006537
|View full text |Cite
|
Sign up to set email alerts
|

Study of the first reported nest of loggerhead sea turtle, Caretta caretta, in the Spanish Mediterranean coast

Abstract: We summarize all the data of nest placement, incubation period, emergence of hatchlings and nest study of the first reported nesting event of a loggerhead turtle Caretta caretta (Reptilia: Cheloniidae) in the Spanish Mediterranean coast. The nest was laid in a beach of Almería province (south-east Spain) in July 2001. The incubation period was 58 days. Forty-two hatchlings emerged from a total of 97 eggs laid. Future beach surveys will determine whether this is a sporadic nesting event or whether loggerheads n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…It is estimated that about 5,000 nests are laid every year in the Mediterranean (Margaritoulis et al 2003), much less than the large rookeries of the Atlantic (about 80,000 nests/year; Ehrhart et al 2003) or the Indian Ocean (about 20,000-40,000 females/year that represents about 70,000-140,000 nests/year; Baldwin et al 2003). Most rookeries are located in the eastern Mediterranean basin (Margaritoulis et al 2003) although sporadic nesting has been reported from the western basin (Llorente et al 1992;Tomas et al 2002;Delauguerre and Cesarini 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that about 5,000 nests are laid every year in the Mediterranean (Margaritoulis et al 2003), much less than the large rookeries of the Atlantic (about 80,000 nests/year; Ehrhart et al 2003) or the Indian Ocean (about 20,000-40,000 females/year that represents about 70,000-140,000 nests/year; Baldwin et al 2003). Most rookeries are located in the eastern Mediterranean basin (Margaritoulis et al 2003) although sporadic nesting has been reported from the western basin (Llorente et al 1992;Tomas et al 2002;Delauguerre and Cesarini 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, despite the lack of scientific reports, interviews with coastal inhabitants indicate that some nesting activity of sea turtles still occurred in the 20th Century on the Spanish Mediterranean coasts (Pascual, 1985;Filella-Subira & Esteban-Guinea, 1992). This fact was confirmed when a loggerhead turtle was observed nesting on a beach of Vera, Almería (south-east Spain) in July 2001 (Tomás et al, 2002). Close monitoring of this nest allowed elucidation of various nest parameters, including an incubation period of 58 days; a clutch size of 97 eggs, and a hatchling emergence success of 41.2% (Tomás et al, 2002).…”
Section: Introductionmentioning
confidence: 76%
“…The low number of adults (CCL ≥ 70 cm) is probably due to the absence of nesting beaches in the region of Morocco and Spain (Tiwari et al, 2001;Tomas et al, 2002) and the absence of smaller individuals (≤50 cm CCL) may partly be explained by the 40 cm mesh size of the driftnets, which could allow smaller individuals to pass through. The majority of captures by surface and bottom longlines were also between 50 and 70 cm CCL.…”
Section: Discussionmentioning
confidence: 99%